The uncertainty in the radon hazard classification of areas as a function of the number of measurements. (July 2017) - Friedmann, H.; Baumgartner, A.; Gruber, V.; Kaineder, H.; Maringer, F.J.; Ringer, W.; Seidel, C.
Abstract: The administration in many countries demands a classification of areas concerning their radon risk taking into account the requirements of the EU Basic Safety Standards. The wide variation of indoor radon concentrations in an area which is caused by different house construction, different living style and different geological situations introduces large uncertainties for any classification scheme. Therefore, it is of importance to estimate the size of the experimental coefficient of variation (relative standard deviation) of the parameter which is used to classify an area. Besides the time period of measurement it is the number of measurements which strongly influences this uncertainty and it is important to find a compromise between the economic possibilities and the needed confidence level. Some countries do not use pure measurement results for the classification of areas but use derived quantities, usually called radon potential, which should reduce the influence of house construction, living style etc. and should rather represent the geological situation of an area. Here, radon indoor measurements in nearly all homes in three municipalities and its conversion into a radon potential were used to determine the uncertainty of the mean radon potential of an area as a function of the number of investigated homes. It could be shown that the coefficient of variation scales like 1/√n with n the number of measured dwellings. The question how to deal with uncertainties when using a classification scheme for the radon risk is discussed and a general procedure is proposed. Highlights: Indoor radon concentrations were measured in nearly all homes in 3 municipalities. The uncertainty of the area mean as a function of the sample size was determined. A decision process based on uncertainties is proposed to define radon-prone areas.